THE CONCEPT OF THE SYARIAH HOTEL IMPLEMENTATION IN THE COTTAGE OF THE WOOD SYARIAH LEMBANG - M Algi Fazza; Rexy Septia H (STIESA Press, 2020)
Lately the development of business with a religious background, namely Islam is becoming more and more prevalent. In addition to banking, insurance, education and others, the concept of sharia was also born in the hotel world. On the one hand the emergence of Islamic hotels in the country deserves thumbs up. Sharia hotel brands as with other sharia products, although perhaps their market share is more specific and highly segmented, it is very possible that in the near future it will be a product that is needed by everyone, not just for the Islamic minority. In addition to hotels, sharia villas and cottages are now also appearing in the city of Bandung, one of which is in the lembang area, namely sharia wooden house cottages. What distinguishes between ordinary cottages with cottages that apply Islamic principles, then whether the existing facilities are still the same as ordinary cottages.